Bioviabilitas Ekstrak Gracilaria sp terhadap Stem Sel Mesenkimal sebagai Terapi Adjuvant Periodontitis - Talsha Irzaputri A; Yoifah Rizka; Sarianoferni (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2016)
Background: Gracilaria Seaweed extracts are known to have an antibacterial content thatcan inhibit the growth of Porphyromonas gingivalis bacteria. P.Gingivalis are dominant inchronic periodontitis as a cause of periodontal tissue damage that can be inhibited by usingmaterials that contain antibacterial effect. Terms of materials to be applied in the oral cavitymust be biocompatible, through toxicity tests, one with bioviability test. In this studybioviability test performed on media mesenchymal stem cells. Purpose: To determinebioviability Gracilaria seaweed extract against mesenchymal stem cells as adjuvant therapyof periodontitis. Materials and Methods: study design was post test only control groupdesign. Mesenchymal stem cells in 96 wells were divided into a control group of cells (n=6),media controls (n=6), and treatment (n=6). The treatment group was given Gracilariaseaweed extract with a concentration of 2.5%, 5%, 10%, 20% and 40%. Stem cells wereincubated 24 hours before and after treatment. Once given MTT, optical density read with anELISA reader then calculated the percentage of living cells. Toxic material when living cells<50% and not toxic when living cells >50%. Living cell data were analyzed by statistical testKruskal Wallis and Man Whitney. Result: Viability cell at 2.5% concentration is 68.59%, 5%concentration = 29.67%, 10% concentration = 4.43%, 20% concentration = 2.5% and 40%concentration = 0.96 %. Conclusion: Extract of seaweed Gracilaria proven not toxic at 2.5%concentration and proved toxic at 5%, 10%, 20% and 40% concentration